If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -16 + 3x = 3 + 6x + -18 Reorder the terms: -16 + 3x + 3x = 3 + 6x + -18 Combine like terms: 3x + 3x = 6x -16 + 6x = 3 + 6x + -18 Reorder the terms: -16 + 6x = 3 + -18 + 6x Combine like terms: 3 + -18 = -15 -16 + 6x = -15 + 6x Add '-6x' to each side of the equation. -16 + 6x + -6x = -15 + 6x + -6x Combine like terms: 6x + -6x = 0 -16 + 0 = -15 + 6x + -6x -16 = -15 + 6x + -6x Combine like terms: 6x + -6x = 0 -16 = -15 + 0 -16 = -15 Solving -16 = -15 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3x+41-4x=2-6x+4 | | 30-(x+5)=8x-2 | | x(x+5)=2x+5 | | 15/h+35=95 | | 35+15/h=95 | | 5m^2-38m-16=0 | | 6+a=10 | | 12x-3=32x+12 | | x/5+5=305 | | A=3b+2 | | -1/2x=1048 | | 0.2+13=1.3-14.5 | | 6+3q=9+2q | | 13-37= | | 10x^2+10x-20=0 | | 2y-2=-6 | | 2y-3=-6 | | X+3=-x+12 | | 2(m-10)+2=24 | | (x+12)(x-2)=1 | | 2x+3=2y-7 | | 2x+6y=-12 | | 7(7-5x)=-38-6x | | x^2-6x-17= | | 9x^2-36+27=0 | | 4(w+8)=5(w-3) | | -4y-8x=8 | | 8m=3+5m | | -5+x=25 | | X^5-x^4-8x^3+12x^2=0 | | y=3600-.8y | | 3(2x^2+17x-9)=0 |